Prolonged-access to cocaine induces distinct Homer2 DNA methylation, hydroxymethylation, and transcriptional profiles in the dorsomedial prefrontal cortex of Male Sprague-Dawley rats. (December 2018) - Ploense, Kyle L.; Li, Xiang; Baker-Andresen, Danay; Carr, Amanda E.; Woodward, Nick; Bagley, Jared; Szumlinski, Karen K.; Bredy, Timothy W.; Kippin, Tod E.
Abstract: Repeated cocaine administration induces many long-term structural and molecular changes in the dorsal medial prefrontal cortex (dmPFC) and are known to underlie aspects of cocaine-seeking behavior. DNA methylation is a key long-lasting epigenetic determinant of gene expression and is implicated in neuroplasticity, however, the extent to which this epigenetic modification is involved in the neuroplasticity associated with drug addiction has received limited attention. Here, we examine the relation between DNA methylation and gene expression within the dorsal medial prefrontal cortex (dmPFC) following limited cocaine self-administration (1 h/day), prolonged cocaine self-administration (6 h/day), and saline self-administration (1 h/day). Rats were fitted with intravenous catheters and allowed to lever press for saline or cocaine (0.25 mg/kg/0.1 mL infusion) in the different access conditions for 20 days. Prolonged-access rats exhibited escalation in cocaine intake over the course of training, while limited-access rats did not escalate cocaine intake. Additionally, limited-access and prolonged-access rats exhibited unique Homer2 epigenetic profiles and mRNA expression. In prolonged-access rats, Homer2 mRNA levels in the dmPFC were increased, which was accompanied by decreased DNA methylation and p300 binding within the Homer2 promoter. Limited-access animals exhibited decreased DNA methylation, decreased DNA hydroxymethylation, and increased p300 binding within the Homer2 promoter. These data indicate that distinct epigenetic profiles are induced by limited-versus prolonged-access self-administration conditions that contribute to transcriptional profiles and lend support to the notion that covalent modification of DNA is implicated in addiction-like changes in cocaine-seeking behavior. Highlights: Rats escalated cocaine use when allowed 6 h of daily self-administration. Rats did not escalate cocaine use when allowed 1 h of daily self-administration. After 6 h of cocaine self-administration, rats exhibited the following epigenetic changes in the dmPFC: o Enhanced Homer2 mRNA expression o Decreased DNA methylation in the Homer2 promoter After 1 h of cocaine self-administration, rats exhibited the following epigenetic changes in the dmPFC: o Decreased DNA methylation in the Homer2 promoter o Decreased DNA hydroxymethylation in the Homer2 promoter o Increased p300 binding in the Homer2 promoter